Incidental detection of achalasia in a patient with dyspnea - Leslie, William; Soekardi, Adi; Icksan, Aziza Ghanie (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Background: The absence of progressive peristalsis in the esophageal body and aberrant relaxation of the LES are two characteristics of achalasia, which is a main motility disease of the esophageal body and lower esophageal sphincter (LES). The most typical signs of achalasia are dysphagia and recurrent regurgitation. Case report: We report a case of achalasia in a 54-year-old woman with the main complaint of dyspnea. Physical examination did not reveal any abnormalities. Chest x-ray results showed an enlarged upper mediastinal with air fluid level and superposition with the right border of the heart. The results of a chest computed tomography (CT) scan showed a dilated esophagus containing food material with air fluid levels. The patient then underwent an esophagostomy thoracotomy. Discussion: Primary achalasia is associated with inflammatory degeneration of the inhibitory ganglion cells of the esophageal myenteric plexus and LES. Dysphagia, regurgitation, problems swallowing food, chest pain, heartburn, and weight loss are the most common symptoms. Barium esophagram is the best diagnostic test for achalasia with